Criminological Analysis of Narcotics Addicts in the Study of Differential Association and Sub Culture Theory (Law Research Review Quarterly, 2020)
The problem of drugs in Indonesia is still something that is urgent and complex. In the past decade this problem has become widespread. Evidenced by the increase in the number of drug abuse or addicts significantly, along with the increasing disclosure of drug crime cases which are increasingly diverse in patterns and increasingly massive in their syndicate networks. Indonesian society, even the world community, in general is currently faced with a very alarming situation due to the rampant use of various types of illegal drugs. This concern is further heightened due to the rampant illegal circulation of narcotics that has spread in all walks of life, including among the younger generation. The behavior of some adolescents who have clearly ignored the values ​​and norms and laws that apply in the midst of community life is one of the causes of the rampant use of drugs among the younger generation. In everyday life in the midst of society there are still many teenagers who still do drug abuse.